EKSPLORASI PENERAPAN SISTEM AMONG KI HADJAR DEWANTARA MELALUI PENDEKATAN PLURALISTIK DALAM PENGELOLAAN KELAS DI SD NEGERI TIMURAN YOGYAKARTA - Dwi Wijayanti; Biya Ebi Praheto (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2020)
This study aims to: (1) Know and explain the application of the system among Ki Hadjar Dewantara through a pluralistic approach in classroom management, (2) Identifying various challenges faced in implementing the application of the Ki Hadjar Dewantara system through a pluralistic approach in classroom management, (3) Knowing and explaining the various efforts made to overcome obstacles in the application of the system among Ki Hadjar Dewantara through a pluralistic approach in classroom management. This research is a qualitative study conducted at the Timuran State Elementary School in Yogyakarta in June-December 2019. Data collection techniques used, namely: direct observation techniques, in-depth interviews, and documentation. The results showed that (1) The Implementation of Among Ki Hadjar Dewantara's System in Classroom Management in Timuran State Elementary School has been going well, namely implemented through a pluralistic approach in which there are 5 types namely instructional approach, authoritarian approach, democratic approach, socio-emotional approach and also the group process approach. (2) several obstacles that become challenges for schools include: the competence of teachers who do not all understand the among systems and also classroom management, heterogeneous student characteristics, incomplete school facilities, and also the lack of support from parents of students. (3) Efforts made by schools to deal with problems include: There is a policy from the school principal to involve teachers in turns in a series of training or training. The teacher makes observation sheets of students to get to know. strengths and weaknesses of students. The school tries to embrace parents in every activity